A framework for analysis of national interest: United States policy toward Taiwan. Issue 1 (2nd January 2016) - Hu, Shaohua
ABSTRACT: The rise of China in the 21st century has generated a new round of debates on American policy toward Taiwan. Generally speaking, one side suggests that Washington should adjust its Taiwan policy to improve its relations with China, while the other argues against downgrading the relations with Taiwan. Both sides invoke the concept of national interest, but the concept is not unproblematic, and cherry-picking different facts and arguments is far from convincing. This article has two purposes: using the concept of national interest to examine the Taiwan policy, and using this case to illuminate the concept itself. After reviewing the concept, I propose what I call 'four Ps' framework to facilitate policy-making and analysis. The framework comprises four factors that help determine which policy is in national interest. They are players (decision makers), preferences (foreign policy goals), prospects (possible outcomes), and power (the capability of achieving goals).